Children’s narratives about play in the context of transition from pre-school to the first elementary school year - Letícia Joia de Nois; Aline Sommerhalder; Luana Zanotto (Revista Diálogo Educacional, 2025)
It aims to examine and problematize, through children’s narratives, the transition from kindergarten to the 1st year of elementary school, where it concerns playing at school. Authors like Formosinho and Brougère were considered, and it took a qualitative-exploratory nature via narrative interviews with 13 children in the last phase of kindergarten and the 1st year of elementary school. Based on Content Analysis, the results of the Play Culture category highlighted activities with water and/or pools; Dress-up and costume games; Tag and hide-and-seek; Sandboxes and Wooden Outdoor Playground. The findings showed children’s favorite games, environments or playful media they wished were available at the schools. The study was indicative of a less stimulating structure in the elementary school facility than in the kindergarten space in the elements: available playtime, playful environments and possibilities for experiences with symbolic games or with the whole body. The authors warn about the needed consideration about childhood staying transient to the 1st year and that the transition between cycles could be more successful if that aspect is valued yet in the perspective of a understanding of learning in continuity, as opposed to a rupture between cycles.